Akuntanbilitas Dan Transparansi Laporan Keuangan Berbasis Teknologi Informasi Pada Badan Amil Zakat Nasional Kabupaten Deli Serdang - Yona Andreani; Laylan Syafina (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
One of the biggest problems in Indonesia is the very high poverty rate. This happens because of the unequal distribution of wealth. The majority of Indonesia's population is Muslim, so to overcome poverty, you can optimize zakat. The potential of zakat in Indonesia can be a solution to alleviate poverty. In an effort to optimize the potential of zakat, the government formed an agency in charge of managing zakat, namely the National Amil Zakat Agency (BAZNAS). Unfortunately, the formation of this agency was not followed by the realization of the potential of zakat funds due to the lack of public trust in BAZNAS. Accountability and transparency of financial reports is very important in managing an agency. With good accountability and transparency, it will provide a good image for the agency so as to increase public trust. In line with this, technological developments cause all fields to be able to adapt by transforming into the digital realm. Accountability and transparency of digital-based financial reports are expected to increase public trust in BAZNAS so that this can be an effort to optimize zakat in Indonesia. This study uses a qualitative approach with primary and secondary data sources obtained from data collection techniques in the form of interviews, observations and documentation. The results of this study can be a solution for BAZNAS which has not maximized the use of technology as a medium to increase transparency and accountability of financial reports which can increase public trust in BAZNAS.